RELASI PRANATA LINGKUNGAN DENGAN LINGKUNGAN HIDUP PERSPEKTIF HUKUM ISLAM - Rifqi Nurdiansyah; Ike Yulisa; Doli Witro; Syamsarina Syamsarina; Zaenab Tri Lestari (Jurnal Integrasi Ilmu Syariah (Jisrah), 2022)
Every human being is a caliph whose role is to provide prosperity for other humans and care for and maintain the environment they inhabit. Islamic teachings have regulated it; so that the principles of life as the main tasks and functions of humans must be following Islamic instructions. This article discusses the relationship between environmental institutions, the environment, and Islamic law and initiates an excellent social life in the view of Islam. This article aims to highlight the relationship between environmental institutions, the environment, and Islamic law. This article uses qualitative research methods that are literature review. The data in the articles are obtained from library materials such as books, articles, etc. related to environmental institutions, the environment, and Islamic law. The data analysis technique used in this article is the qualitative data analysis technique of Miles et al. namely data condensation, data presentation, and drawing conclusions. The results of the analysis show that environmental institutions are closely related to Islamic law, namely that Islam has given rules and assignments to humans to become caliphs on earth to manage nature as well as possible, in accordance with the rules that have been explained in the Koran and the rules regarding nature or the environment that made by humans themselves without violating what has been determined by God. Preserving the environment can be done by empowering as best as possible, the full environmental empowerment system in Islam that emphasizes the public benefit.